First record of Dihammaphora (Coleoptera, Cerambycidae, Cerambycinae, Rhopalophorini) for Venezuela: description of a new species and updated key to species of Dihammaphora with 11 antennomeres - Ferreira, Gabriel S.; Cazorla, Dalmiro; Alarcón, Maritza; Mermudes, José Ricardo M. (Zootaxa, 2025)
Dihammaphora meridensis sp. nov. is described from Mérida (Venezuela), representing a new country record for the genus. A key to species of Dihammaphora with 11 antennomeres is provided.